Inscribed Seals. First Temple Period. Hebrew, Ammonite, Moabite, Phoenician and Aramaic. From the Collections of the Israel Museum and the Israel Department of Antiquities and Museums - Hestrin, Ruth (1979)
no. 136: Assyrian cylinder seal with Aramaic inscriptian l-šlm (Slg. E. Borowski, Basel, No.65.11.5).